Evidence-based hamstring injury prevention and risk factor management: A systematic review and meta-analysis of randomized controlled trials - Rudisill, S. S.; Vardy, N. H.; Kucharik, M. P.; Eberlin, C. T.; Martin, S. D. (The American Journal of Sports Medicine, 2023)
Background: Hamstring injuries are common among athletes. Considering the potentially prolonged recovery and high rate of recurrence, effective methods of prevention and risk factor management are of great interest to athletes, trainers, coaches, and therapists, with substantial competitive and financial implications.